Multi‐phase Extraction of Glycoraphanin from Broccoli Using Aminium Ionic Liquid‐based Silica. Issue 1 (9th July 2012) - Tian, Minglei; Bi, Wentao; Row, Kyung Ho
ABSTRACT Introduction Glucosinolates, a class of phytochemicals found in broccoli, have attracted recent interest due to the potential health benefits associated with their dietary intake. Glucoraphanin, the most common glucosinolate in broccoli can be converted to a known cancer chemopreventive agent. Multi‐phase extraction in solid‐phase extraction cartridges was developed to simultaneously extract and separate this compound. Objective Multi‐phase extraction with functionalised ionic liquid‐based silica as a sorbent was used to simultaneously extract and separate glucoraphanin from broccoli. Methodology The sorbent and broccoli sample were packed into a single cartridge, and a fixed volume of water was then used to extract and remove the target compound from the sample to the sorbent over 15 repetitions. The sorbent was then washed with n‐hexane to remove any interference and the target compound was eluted with water–1% acetic acid (vol.). Results Under the optimised condition, 0.038 mg/g of glucoraphanin was obtained by multi‐phase extraction with 0.2 g of sorbent. Conclusion The adsorption isotherm allowed investigation of the interactions between the sorbent and target compound and provided evidence for the accuracy of this method. The low deviation error, small amount of solvents required, highly selective separation and stability of the method justify further research. Copyright © 2012 John Wiley & Sons, Ltd.